2004
DOI: 10.4161/cbt.3.6.848
|View full text |Cite
|
Sign up to set email alerts
|

HOXA10 Regulates p53 Expression and Matrigel Invasion in Human Breast Cancer Cells

Abstract: HOX genes regulate cell differentiation during embryonic development. Here we demonstrate HOXA10 expression in both benign and malignant adult human breast tissue and in MCF-7, but not BT20 breast cancer cells. We have previously shown that HOXA10 mediates uterine differentiation in response to estrogens. The mechanism of action of estradiol and other estrogen receptor modulators on breast cancer cell growth is still poorly understood. MCF-7 cells, which are ER (+) and express HOXA10, were used to assay the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 29 publications
4
69
0
2
Order By: Relevance
“…Hox gene expression is linked to apoptosis and angiogenesis. Hoxa5 and Hoxa10 can regulate p53 expression in human breast cancer cell lines (10,11). Induction of HOXA5 expression causes caspase 2-and caspase 8-mediated apoptotic cell death (32).…”
Section: Ncammentioning
confidence: 99%
See 1 more Smart Citation
“…Hox gene expression is linked to apoptosis and angiogenesis. Hoxa5 and Hoxa10 can regulate p53 expression in human breast cancer cell lines (10,11). Induction of HOXA5 expression causes caspase 2-and caspase 8-mediated apoptotic cell death (32).…”
Section: Ncammentioning
confidence: 99%
“…Specific roles for Hoxb3 and Hoxd3 in cell proliferation have been reported during hematopoesis and angiogenesis (8,9). Additionally, Hoxa5 and Hoxa10 regulate P53 expression in human breast cancer cells (10,11).…”
mentioning
confidence: 99%
“…HOXA10 has a role in invasion of breast cancer cells 27 and HOXB13 has been shown to be associated with differentiation of epidermal tissues. 28 These data show that the HOX genes have multiple roles in human developmental processes and the association of HOX genes with several types of cancers may be one of the functions of HOX genes.…”
mentioning
confidence: 99%
“…Moreover, there is evidence that HOX, MEIS and PBX genes are involved in oncogenic processes, such as chromatin binding, cell cycle control, proliferation, apoptosis, angiogenesis and cell-cell communications. 3,7,25,28,[32][33][34][35][36][37][38][39] It has been shown that in the normal endometrium MEIS1 protein was expressed in early proliferative glandular epithelium and was absent throughout the rest of the cycle, suggestive of a function in proliferation for MEIS1. 25 Furthermore, after exposure of the ovarian surface epithelium cell line MCV152 to follicle-stimulating hormone, cell proliferation was increased and MEIS1 expression was up-regulated.…”
mentioning
confidence: 99%